Damage analysis of rotation speed on corrosion film of 3Cr steel in the CO2 environment with silty sand. (March 2022) - Zhao, Yonggang; Liu, Wei; Dong, Baojun; Chen, Longjun; Fan, Yueming; Zhang, Tianyi; Yang, Weijian
Highlights: Corrosion resistance of 3Cr steel was first reduced, followed by enhancing and then reduced as the rotation speed increased. Silty sand changed from participating in the corrosion film to destroying the corrosion film. Increasing rotation speed converted a factor that played a dominant role in corrosion resistance from mass transfer process to shear stress of silty sand. Critical rotation speed for corrosion mechanism transformation of 3Cr steel was 600 r/min. Abstract: The 3Cr steel used as the tubing has serious corrosion damage in a flowing CO2 environment with silty sand. Hence, the investigation for the influence of flow velocity on the corrosion behavior of 3Cr steel has an important and practical significance. It could not only unveil the corrosion damage mechanism of the steel under dynamic conditions, but also provide a theoretical basis for the corrosion protection of the tubing. In this paper, the effect of flow velocity on the corrosion film of 3Cr steel in a CO2 environment with silty sand was investigated by adjusting rotation speed. The results revealed that the corrosion resistance of 3Cr steel was first reduced, followed by enhancing and then reduced as the rotation speed increased. There was a critical rotation speed for the transformation of corrosion mechanism of 3Cr steel, i.e., 600 r/min. When the rotation speed was lower than the critical speed, the mass transfer process of corrosive medium dominated the corrosion resistance of 3Cr steel, and silty sand participated in the formation of corrosion film. The increasing rotation speed accelerated the mass transfer process, which first reduced and then improved the corrosion resistance. When the rotation speed was higher than the critical speed, the shear stress of silty sand played a predominant role. At the same time, silty sand impinged on the corrosion film, and then destroyed the stability of the film, leading to a significant decrease of the corrosion resistance. Silty sand changed from participating in the corrosion film to destroying the corrosion film with increasing rotation speed.